NEXUS Gains in the Incomati and Limpopo basins: Botswana, Eswatini, Mozambique, South Africa, and Zimbabwe. - CGIAR Initiative on NEXUS Gains (International Water Management Institute, 2024)
A NEXUS Gains transboundary river basin brief shares examples of the Initiative’s work across five work packages in the Incomati Basin and Limpopo Basin – specifically the Shashe sub-basin – covering Botswana, Eswatini, Mozambique, South Africa, and Zimbabwe.